BOLA HUQUQLARINING KAFOLATLARI VA UNI BUZGANLIK UCHUN MA’MURIY JAVOBGARLIK - Kudaybergenova, T.K. (SCIENCE and SOCIETY, 2025)
This article examines the rights of children, their legal framework, the guarantees ensuring these rights, and the administrative accountability for any breaches. It further offers recommendations on how to prevent legal violations connected to neglecting responsibilities in the upbringing and education of children.